Promoting Islamic Character Education in Inclusive Schools: Lessons Learned from the Supporting and Inhibiting Factors - Meliani, Fitri; Hambali, Adang; Yuliati Zaqiah, Qiqi; Sulhan, Mohammad (International Journal of Education and Digital Learning (IJEDL), 2024)
Initiatives to advance fairness and inclusion in educational systems should be founded on an examination of specific settings. This article presents a framework that is founded on research and may be applied to such contextual studies. This piece is a qualitative approach and is presented descriptively. The school principal, teachers, and students in inclusive schools served as the study's primary sources. Students cited supportive relationships, positive teacher beliefs, positive school leader attitudes, supportive teaching practices, and accessibility as five aspects that encourage inclusive education. The findings reveal a variety of barriers and challenges in educational settings, including a lack of teacher preparation that is necessary to meet the needs of all students, the recognition that student diversity is a challenge, physical barriers, underutilization of available resources, and an educational response devoid of organizational and didactic strategies that do not assume responsibility for a fair and inclusive curriculum for all students. It is clear that Islamic character education requires constant habituation and intervention, refuted and carried out consciously by each component. The need for continued professional development and opportunities to improve pre-service teacher education programs are explored.